Medically unexplained symptoms in primary health care - Sturla Brynjólfsson 1988- (2018)
Medically unexplained symptoms (MUS) are somatic symptoms which have little or no physical explanation. Examples of MUS are dizziness, fatigue, pain, headaches, visual and auditory interference and changes in gut motility. Prevalence of MUS in primary care varies between studies, but is usually around 30%. It is estimated that MUS patients have double the outpatient and inpatient medical care utilization compared to non-MUS patients. Previous studies have found significant, positive correlation between the number of lifetime MUS and current and past exposure with anxiety and depression. The aim of the study was to: 1) Evaluate the prevalence of MUS at the primary health care in Reykjavík, 2) find out how much MUS interferes with patients’ daily life and 3) assess the correlation between MUS and psychiatric morbidity. Participants were 106 patients visiting two primary health care clinics in Reykjavik. Having one or more MUS that clearly interferes with daily life was reported by 24.5% of the patients. The most frequent MUS were related to fatigue and muscle problems. Among all the participants, 28.3% reported symptoms which reached to a clinical point of either depression, general anxiety or health anxiety. There was a significant, positive correlation between depression, anxiety and MUS. These findings are consistent with previous studies.